The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/jcm9020514
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mortality among Patients with Pseudomonas aeruginosa Bloodstream Infections: What Is the Influence of XDR Phenotype on Outcomes?

Abstract: This study aimed to assess the impact of extensively drug-resistant (XDR) phenotype on mortality in Pseudomonas aeruginosa bacteremia. A retrospective cohort study was performed in a tertiary hospital from January 2000 to December 2018. All consecutive prospectively recorded P. aeruginosa bacteremia in adult patients were assessed. In this study, 382 patients were included, of which 122 (31.9%) due to XDR P. aeruginosa. Independent factors associated with 14-day mortality were as follows: high-risk source of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 48 publications
1
18
3
Order By: Relevance
“…18 P aeruginosa is a versatile bacterium that poses challenges to clinicians due to its exceptional ability to develop additional resistance by the selection of gene mutation and selection of multidrug resistance status. 24 While previous studies identified a higher mortality rate among patients with MDR P aeruginosa BSIs than non-MDR, our study did not find any statistically significant difference. 25,26 In our study, 34.8% of the tested P aeruginosa isolates were resistant to imipenem, and 35.2% were resistant to meropenem.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…18 P aeruginosa is a versatile bacterium that poses challenges to clinicians due to its exceptional ability to develop additional resistance by the selection of gene mutation and selection of multidrug resistance status. 24 While previous studies identified a higher mortality rate among patients with MDR P aeruginosa BSIs than non-MDR, our study did not find any statistically significant difference. 25,26 In our study, 34.8% of the tested P aeruginosa isolates were resistant to imipenem, and 35.2% were resistant to meropenem.…”
Section: Discussioncontrasting
confidence: 95%
“…A retrospective study by Tumbarello et al reported 12.5% of P aeruginosa BSIs as MDR based on the same criteria we used 18 . P aeruginosa is a versatile bacterium that poses challenges to clinicians due to its exceptional ability to develop additional resistance by the selection of gene mutation and selection of multidrug resistance status 24 . While previous studies identified a higher mortality rate among patients with MDR P aeruginosa BSIs than non‐MDR, our study did not find any statistically significant difference 25,26 …”
Section: Discussioncontrasting
confidence: 71%
“…The primary site of infection was defined as the most possible source of infection responsible for P. aeruginosa bacteremia on the basis of medical records, including lung infection, soft-tissue infection, biliary tract infection, urinary tract infection, catheter-related infection and peritoneum infection. 23 It was defined as the bacteremia of unknown origin when the source of the infection was unclear. 23 Nosocomial infection was defined as the P. aeruginosa bacteremia (1) that occurred more than 48 h after admission to hospital, or (2) that occurred less than 48 h after admission to hospital in cases who had been hospitalized in other hospitals within the 2 weeks prior to admission.…”
Section: Methodsmentioning
confidence: 99%
“… 23 It was defined as the bacteremia of unknown origin when the source of the infection was unclear. 23 Nosocomial infection was defined as the P. aeruginosa bacteremia (1) that occurred more than 48 h after admission to hospital, or (2) that occurred less than 48 h after admission to hospital in cases who had been hospitalized in other hospitals within the 2 weeks prior to admission. 16 , 17 Community-acquired infection was defined as the P. aeruginosa bacteremia that occurred less than 48 h after admission to hospital in patients who had never been in hospital or nursing home.…”
Section: Methodsmentioning
confidence: 99%
“…Infection epidemiology in hospitalized patients has exhibited a changing profile in the last few decades in Brazil, with significant increases in Gram-negative bacilli (GNB), as well as a progressive rise in multidrug-resistant (MDR) strains. For this reason, inappropriate empirical antibiotic treatment of patients presenting infection by multidrugresistance bacteria has become a major challenge [1][2][3]. Information regarding the current impact of inappropriate therapy on patients with nosocomial infection, however, is lacking.…”
Section: Introductionmentioning
confidence: 99%